An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Beltrán, Samarkanda (2010)
Taking into account that reading is an ability that learners must acquire in the process of mastering a foreign language in any educational system the present research work is aimed to do an analysis on the suitability of selected newspaper material as a teaching resource in ESL courses. This research was made through collecting different kinds of international Newspapers (Britain/American) and selecting Articles, Reports, News and Ads; they were the principal resource to get the information required.